Management of paediatric otogenic cerebral venous sinus thrombosis: a systematic review. (December 2015) - Wong, B.Y.W.; Hickman, S.; Richards, M.; Jassar, P.; Wilson, T.
Abstract : Background: Otogenic paediatric cerebral venous sinus thrombosis (CVST) is rare but has potential clinical sequelae. Its management has long been debated mainly concerning the role of surgery and the use of anticoagulant therapy. Objective of review: To review the current literature and examine the medical and surgical management of paediatric otogenic CVST and its clinical and radiological outcome. Type of review: Systematic review. Search strategy: The electronic databases (MEDLINE, EMBASE, Cochrane) were searched from inception to November 2014 using text words 'cerebral venous sinus thrombosis OR cerebral venous thrombosis OR lateral sinus thrombosis OR sigmoid sinus thrombosis' AND 'otogenic OR mastoiditis OR otitis media' AND 'children OR paediatric OR pediatric'. Evaluation method: Inclusion criteria were applied by two reviewers and data extraction was carried out. The type of otological surgery (conservative versus extensive) and the use of anticoagulants with their clinical and radiological outcomes were tabulated. Results: Thirty‐six studies (15 case reports and 21 case series) were included with a total of 190 patients. A total of 92.1% of patients underwent otological surgery, and 69.5% had conservative surgery and 30.5% extensive otological surgery. Anticoagulants were used in 59%. A total of 79.2% of patients were reported to have had a good clinical outcome. Within this group, 56% had conservative surgery and anticoagulants. Follow‐up scans were documented in 61.6% of patients and complete recanalisation was observed in 51%. Complete recanalisation was observed in 47% of those who had been anticoagulated and 55% of those who received no anticoagulation. Conclusions: Conservative otological surgery with the combination of anticoagulation was the most common treatment modality found in the group of patients with good clinical outcome. However, given the current low level of evidence, a multicentre collaborative study is needed to help establish the optimum surgical approach and the role of anticoagulation in managing paediatric otogenic CVST.